The Effectiveness of Peacekeeping as a Management Tool for Political Crisis: A Case Study of Somalia - Opio, Richard B. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Since the ouster of the dictator Siyad Barre in 1991, Somalia has gone through years of turmoil and terrible humanitarian crisis. The situation in Somalia metamorphoses from one picture to another with no sign of moving in a positive direction. Since the time the international community decided to respond from 1992 to date, peace and security has eluded the ordinary people of Somalia; who continue to live in squalid and dangerous conditions that has cost the failed state millions of life. This thesis sought to examine the efforts by the international community to stabilize Somalia. The findings reveal that the biggest problem of all these efforts have been attempts to export, copy and paste solutions foreign to the life and uniqueness of the clan-based system of allegiance. I conclude that a solution to Somalia's political fiasco lies with the people of Somalia through a sustained dialogue that will build a contextual solution to its settings.